Brand Relationship and Its Effect Towards Brand Evangelism to Banking Service - Riorini, Sri Vandayuli; Widayati, Christine Catur (International Research Journal of Business Studies, 2015)
The purpose of this study was to analyze the effect of Brand relationship, Brand trust, Brand identification, Brand involvement,Brand commitment to Brand evangelism. This study using purposive sampling technique in which samples were selected in this study as much as 200 commercial Banks customers have used the services of the Bank at least 12 months. Data analysis instrument used was Multiple Regression Analysis with SPSS assistance. The results obtained are consistent with previous studies, in which customers increasingly have a relationship, trust, identification, involvement, and commitment to the brand Commercial Bank will increasingly have the intention to buy the brand, reference brand they use positively, and give contradictory references the back of a competing brand to others or called with Brand evangelism. Furthermore, it is known that the most dominant factor influencing Brand evangelism is a Brand commitment. Further research is recommended to investigate the influence of Brand relationship with all of its dimensions, namely Brand trust, Brand identification, Brand involvement, Brand commitment to Brand evangelism with its entire dimension (Positive brand referrals, Brand purchase intention, and Oppositional brand referrals). Furthermore, it also is advisable to do research for brands other services, such as hotels and restaurants.